Morphometric and quantitative characterization of atrial ganglion neurons from the intercaval region in dogs with dilated cardiomyopathy - Camacho, Aparecido Antonio [UNESP]; Oliveira-Alves, R.; Klein, R.P.; Sousa, M.G. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2007)
Avaliaram-se quantitativa, morfométrica e qualitativamente os neurônios atriais da faixa intercaval de cães com cardiomiopatia dilatada (CMD). Os neurônios dos gânglios nervosos de cães com CMD eram maiores que os dos cães controle. A histopatologia do miocárdio ventricular e dos neurônios ganglionares confirmou a CMD e demonstrou evidente processo degenerativo neuronal ganglionar. Cães com CMD em fase crônica apresentavam cardioneuropatia secundária, provavelmente pela privação da inervação parassimpática cardíaca.

The quantity, morphometry, and quality of atrial neurons from the intercaval region in dogs with dilated cardiomyopathy (DCM) were evaluated. Dogs with DCM had greater ganglion neurons than control dogs. The histologic evaluation of the ventricular myocardium and ganglion neurons confirmed DCM and showed the degeneration of ganglion neurons. Dogs with chronic DCM had a secondary cardioneuropathy owing to impaired parasympathetic neural control.
Caracterização morfométrica e quantitativa dos neurônios ganglionares atriais da faixa intercaval de cães com cardiomiopatia dilatada
Keywords: Dog; cardiomyopathy; Histology; Morphometry; Cão; Miocardiopatia; Histologia; Morfometria